Rawat Inap Berbasis Data Demografi di Rumah Sakit Swasta Yogyakarta Tahun 2022 - Ardea, Rosa Lintang; Widiantoro, Margareta Stellavia; Kurniastuti, Margaretha (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Introduction: UTI (Urinary Tract Infection) is an infection that occurs in the urinary tract. Risk factors for the occurrence of UTIs include being continuous with demographic data such as age, gender, occupation and education. Objective: to find out the description of the incidence of UTIs based on demographic data of inpatients in hospitals in Yogyakarta in 2022. Methods: This type of research is quantitative descriptive with a total of 686 respondents using total sampling techniques. The variables studied were respondent characteristics including age, gender, occupation and education (independent variables) and UTI (dependent variable). The research location was carried out in the inpatient room at a private hospital in Yogyakarta City. Results: The results of the study showed that the incidence of UTI based on age was found in the elderly group (age > 66) as many as 265 cases (38.6%), female sex as many as 456 cases (66.5%), other types of work, namely housewives, as many as 174 cases (25.4%), based on education in the high school education group there were 228 cases (33.2%). Conclusion: Patients are expected to apply genital hygiene and personal hygiene correctly. Nurses need to carry out catheter installation procedures according to the SOP and provide health education to patients at risk of UTI.